The relationship between the living environment and remote working: an analysis using the SHEL model - Doi,Toshihisa (PeerJ, 2024)
Objective This study investigates the relationship of living environment factors with satisfaction, work engagement, perceived productivity, and stress among teleworkers. Background Given the increase in telecommuting since the onset of the pandemic, the study aims to identify how to create an optimum environment for telecommuting workers. Methods By examining the relationships among these factors via multiple regression analysis, a comprehensive investigation of the telecommuting working environment is conducted, encompassing physical aspects and facilities as well as lifestyle rhythms and relationships with housemates. In doing so, the author identifies measures to create a more favorable living environment. The work environment of remote workers is examined from various perspectives using the framework of the SHEL model: Software (work content, lifestyle, etc.), Hardware (furniture, equipment, etc.), Environment (indoor environment), and Liveware (relationships with family members who reside with the worker). Results The results suggest that positive factors, such as satisfaction and work engagement, are strongly influenced by the degree of job autonomy and the availability of a workspace dedicated to personal use. Negative aspects, such as stress, are significantly impacted by environmental noise, interruptions due to household tasks, and the use of ergonomic furniture.
Keywords: Work from home; Telecommuting; SHEL model; Living environment